Ovarian Oxidative Stress Induced Follicle Depletion After Zona Pellucida 3 Vaccination Is Associated With Subfertility in BALB/c Mice - Zhang, Beibei; Qu, Guanggang; Nan, Yuchen; Zhou, En-Min (Frontiers in Veterinary Science, 2022)
Impaired follicular development associated with autoimmune ovarian disease (AOD), is a typical side effect of ZP3 vaccine-induced subfertility and contributes to the fertility decline, but the mechanism is unknown. In this study, a AOD model was established with recombinant mouse zona pellucida 3 (mZP3) protein in the BALB/c mice, and co-administrated with 0.5 mg/kg antioxidant stress drug sodium selenite (SS), whereas intraperitoneal injection was used and the relationships among oxidant stress (OS), follicle loss and fertility were evaluated. Here we demonstrated that ZP3 vaccination elicited high antibody titers and correlated with reductions of ovarian follicle numbers in both fertile and infertile mice, whereby magnitudes of both factors were negatively correlated with litter size. Moreover, increased OS in ovaries of mZP3-immunized mice was related to high levels of reactive oxygen species (ROS) and malondialdehyde (MDA), and is accompanied by a decrease in the total antioxidant capacity (TAC) of ovaries. Meanwhile, activation of caspase-3 and caspase-9 along with increased Bax and decreased Bcl-2 levels were observed, indicating the ongoing apoptosis of ovarian cells. Notably, inhibition of OS with SS reduced ovarian ROS and apoptosis levels, which was consisted with restoration of follicle numbers. More importantly, SS treatment when co-administered concurrently with mZP3 immunization led to significantly improved fertility (P < 0.05) and the average litter size of the mZP3-vaccinated SS-treated group increased by ~29.2% as compared with that of the vaccinated but untreated group. In conclusion, infertility caused by ZP3 vaccination was mechanistically associated with ovarian OS which triggered depletion of ovarian follicles.